A Bibliography of Koran Texts and Translations - Woolworth, Sage, Jr. (The Muslim world, 1927)
This list, although so carefully prepared, is necessarily still incomplete and subject to revision and additions. The writer gives twenty-seven Arabic printed texts; seven Arabic selections; nine English translations; eleven English translations, selections; six French translations; four French translations, selections; thirteen German translations; six German translations, selections; five Latin translations; three Latin translations, selections; one Hungarian translation; one Czech translation; five Dutch translations; one Greek translation; one Hebrew translation; one Hindi translation; one Hindustani translation; four Italian translations; three Persian translations; one Polish translation; one Russian translation; one Spanish translation; two Swedish translations; one Turkish translation; three Urdu translations. The total number of texts and translations here listed is one hundred and eighteen. For additional information and facsimiles of some Oriental versions see The Moslem World Vol. V. pp. 244-261. Editor.